Shareholding patterns and financial performance: evidence from the banking sector in Bangladesh / Mohammad Kamal Hossain - Hossain, Mohammad Kamal (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
This study attempts to examine the relationship between shareholding patterns and banks’ financial performance, as defined from three different dimensions, namely, profit-based performance measured by return on equity (ROE), market-based performance measured by Tobin’s Q (TQ) and valuebased performance measured by economic value added (EVA). It included 29 out of the 30 banks listed on the Dhaka Stock Exchange for the period 2013–2017, providing a balanced panel with 145 observations. All data were collected from the annual reports of the respective banks. The randomeffects GLS regression model was employed to test the chosen hypotheses. This study found a conflicting result, i.e. there was a relationship between some, but not all of the patterns of shareholdings and financial performance of the listed banks in Bangladesh. For example, a significant relationship between foreign shareholding and banks’ financial performance, as measured by ROE, TQ and EVA-log, was found. Sponsor-directors and general public shareholdings were found to be significantly related to ROE and EVA-log, but insignificantly associated with TQ. However, institutional and government shareholdings were insignificantly related to the banks’ financial performance, regardless of the measures employed to assess it. This study contributes to the existing literature by exploring the relationship between shareholding patterns and banks’ financial performance, and may indicate the need for a restructuring of the existing shareholding patterns in the banking sector in Bangladesh in order to maximise performance. This study is distinctive compared to prior studies, as it examines the relationship between the shareholding patterns disclosed in the annual reports of the sampled banks and banks’ performance, as measured by EVA-log along with ROE and TQ, which have not been covered earlier.